1996
DOI: 10.1139/x26-082
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of soil compaction on growth of Pinuscontorta seedlings

Abstract: A growth chamber experiment was conducted with Pinuscontorta Dougl. ex Loud. var. latifolia Engelm. seedlings grown in soil compacted at 0.1, 2.0, 4.0, 6.0, and 8.0 MPa pressure. Three moisture regimes were applied factorially to compaction levels by watering from above or by maintaining 2- or 10-cm water tables at the base of the 40-cm soil columns. All treatments were grown at either 22:14 °C or 26:18 °C (light:dark) for 13 weeks. Soil compaction increased bulk density, penetrometer resistance, and soil CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
2
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 0 publications
4
36
2
3
Order By: Relevance
“…However, the levels of soil CO 2 observed confirmed results from other laboratory experiments which showed that soil compaction led to large rises in soil CO 2 gas levels (Asady and Smucker 1989;Zainol et al 1991;Conlin and van den Driessche 1996a). Differences in soil CO 2 gas levels were also influenced by the year in which samples were collected.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…However, the levels of soil CO 2 observed confirmed results from other laboratory experiments which showed that soil compaction led to large rises in soil CO 2 gas levels (Asady and Smucker 1989;Zainol et al 1991;Conlin and van den Driessche 1996a). Differences in soil CO 2 gas levels were also influenced by the year in which samples were collected.…”
Section: Resultssupporting
confidence: 84%
“…On the other hand, soil O 2 concentration in these experiments did not decrease to levels that would have inhibited root growth. In addition, Conlin and van den Driessche (1996a) showed that although soil compaction influenced seedling growth, soil ethylene concentrations could not be correlated with either compaction or growth. This led to our conclusion that soil CO 2 may influence plant growth in compacted soils.…”
mentioning
confidence: 95%
“…Our results showed reduced survival after two growing seasons, which may reflect the longer-term implications on seedling survival and we observed similar differences in root growth as those observed by Conlin and van den Driessche (1995). For these reasons, and also because of the possible longer-term implications of the chlorosis we observed for trees exposed to wet soil conditions, short-term results should be used with caution for making recommendations associated with management of long-lived crops such as trees.…”
Section: Discussionsupporting
confidence: 87%
“…In a short-term study, Conlin and van den Driessche (1995) showed that compaction had a small and variable effect on seedling height, but that other responses included decreased needle length, root dry weight, and net photosynthesis. Our results showed reduced survival after two growing seasons, which may reflect the longer-term implications on seedling survival and we observed similar differences in root growth as those observed by Conlin and van den Driessche (1995).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of intensive harvest and site preparation on soil properties and tree growth can be positive, detrimental, or inconsequential (Miller et al 2004). Soil compaction (Hatchell et al 1970, Steinbrenner andGessel 1955), usually indexed by bulk density or soil strength measurements Sands 1980, Powers et al 1998), reduces tree growth under certain conditions (Conlin and van den Driessche 1996, Froehlich et al 1986, Murphy 1983, Wert and Thomas 1981. On some sites, however, soil compaction has resulted in increased tree growth, probably because of increased water-holding capacity (Ares et al 2005, Gomez et al 2002b), unsaturated waterflow (Sands et al 1979), root contact with soil (Bhadoria 1986), and N uptake (Gomez et al 2002a).…”
Section: Impacts Of Ground-based Harvestingmentioning
confidence: 99%